Peculiarities of preparing and performing an investigative experiment when investigating crimes against road safety and transport operation - Kolesnik, H. R. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2019)
This article defines the place and role of the pre-trial investigation authorities in the process of combating crime and justified the author's vision more clearly define their function in criminal proceedings under the Criminal Procedure Code ofUkraine.